Recent Advancements on The Treatment of Systemic Sclerosis: A Review - Ara, Rowsan; Alam, Md. Zahid; Ahsan, Hafez Mohammad Nazmul; Shazzad, Md. Nahiduzzaman (Journal of Shaheed Suhrawardy Medical College, 2012)
J Shaheed Suhrawardy Med Coll ?Volume 2 Number 2 December 2010 ? Page 18-23 DOI: http://dx.doi.org/10.3329/jssmc.v2i2.12048